Evaluation of apical transportation and apical root sealing in root canals prepared with mtwo rotary system with and without apical enlargement – an in vitro study (Bioscience Journal, 2021)
The aim of this study was to evaluate apical transportation and apical root canal sealing after root canal filling in human teeth prepared with MTwo® Rotary System with and without apical foramen enlargement. Twenty mandibular premolars were divided into two groups (n=10). Group 1 had root canals prepared 1mm beyond the apical foramen. Group 2 had root canals prepared 1mm below the root canal length. After chemo-mechanical preparation, samples were submitted to scanning electronic microscopy. Apical foramen images had 75x magnification at standardized positions, allowing measurements from the apical foramen area before and after root canal preparation, and after root canal filling. Apical foramen shape and apical transportation, as well as its level of circumferential filling after root canal preparation were accessed using the Image Subtraction System. Scanning electronic microscopy analysis demonstrated that samples of Group 1 showed larger foraminal diameter than samples of Group 2 (p